Hubungan Merokok Bernikotin terhadap Penurunan Volume Saliva pada Perokok di Kabupaten Tulungagung (Relationship of Smoke Containing Nicotine to Decrease in the Volume of Saliva in Smokers at Tulungagung District) - Ichdanisa Fitriasani; Pujiana Endah Lestari; Leni Rokhma Wati (Pustaka Kesehatan, 2017)
Back Ground: Nicotine is one of the contents of cigarette that bad for health. Nicotine has an influence on the nervous system, which one led to decrease in saliva production. Object: Tulungagung is a district where has a high number of smokers, also there is an identical smoking habit called nyethe. The aim of this study was to determine relationship of the effect of smoking that contains nicotine to decreased in saliva production. Method: The research method used an analitic obsevational study with cross sectional observation. The study was conducted by taking saliva samples of 100 smokers and 100 non smokers at district Tulungagung. Result: The pearson correlation test result showed that the significancy value (sig (2-tailed)) was 0.00 which was smaller than α (0.05) and had a value of peason correlation 0f -0,566. Conclusion: The test result obtained from the pearson correlation was able to explained that nicotine had a relation with saliva volume decreased. The result showed that smoke containing nicotine had influence on reducing the volume of saliva, more often smoke containing nicotine so the lower volume of saliva produced. Keywords: cigarette, nicotine, saliva, tulungagung